2022
DOI: 10.3390/cells11010169
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 at Striatal Synapses: Cell-Type Specificity and Mechanistic Insights

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) cause Parkinson’s disease with a similar clinical presentation and progression to idiopathic Parkinson’s disease, and common variation is linked to disease risk. Recapitulation of the genotype in rodent models causes abnormal dopamine release and increases the susceptibility of dopaminergic neurons to insults, making LRRK2 a valuable model for understanding the pathobiology of Parkinson’s disease. It is also a promising druggable target with targeted therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 133 publications
0
15
0
Order By: Relevance
“…By binding to receptor tyrosine kinases, cognate neurotrophic factors plastically shape neuronal activity 40 . Brain-derived neurotrophic factor (BDNF) is particularly important to modulate cortico-striatal neurotransmission 41 , a circuitry relevant for PD where LRRK2 expression is higher compared to other brain regions 42,43 . To address whether LRRK2 Ser935 phosphorylation is stimulated by BDNF, we prepared primary mouse cortical neurons from C57BL/6J wild-type mice and stimulated them with 100 ng/ml of BDNF at days in vitro 14 (DIV14) when synapses are fully functional ( Figure 1a ) and LRRK2 expression is detectable 44 .…”
Section: Resultsmentioning
confidence: 99%
“…By binding to receptor tyrosine kinases, cognate neurotrophic factors plastically shape neuronal activity 40 . Brain-derived neurotrophic factor (BDNF) is particularly important to modulate cortico-striatal neurotransmission 41 , a circuitry relevant for PD where LRRK2 expression is higher compared to other brain regions 42,43 . To address whether LRRK2 Ser935 phosphorylation is stimulated by BDNF, we prepared primary mouse cortical neurons from C57BL/6J wild-type mice and stimulated them with 100 ng/ml of BDNF at days in vitro 14 (DIV14) when synapses are fully functional ( Figure 1a ) and LRRK2 expression is detectable 44 .…”
Section: Resultsmentioning
confidence: 99%
“…In this context, our research group identified relations of the Lrrk2 gene, until then associated with Parkinson’s and inflammatory bowel diseases, in preference behavior and loss of control by alcohol in mice, Zebrafish, and humans ( 31 , 32 , 36 , 108 110 ). This gene is involved in neural processes, such as the reuptake of synaptic components and synaptic plasticity, and in several signaling pathways by performing GTPase and kinase functions, which influence processes such as cell proliferation and differentiation, apoptosis, inflammation, and immune response ( 50 , 111 116 ). Evidence in humans and mice corroborates with the results of this study regarding the differential regulation with Lrrk2 downregulation to alcohol intake.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some of these genes may have been more relevant to embryonic deletion as compared to the obvious receptor and scaffolding candidates discussed above. For example, Leucine-rich repeat kinase 2 ( Lrkk2 ) is highly expressed in the SPNs 48, 7072 and plays a critical role in regulating synaptogenesis and corticostriatal glutamatergic synaptic function 47, 73, 74 . Another gene of interest, Protein phosphatase 1 regulatory inhibitor subunit 1B ( Ppp1r1b, also known as DARPP32) is critical for the corticostriatal synaptic plasticity and controls both long term potentiation and depression in the striatum 4446 .…”
Section: Discussionmentioning
confidence: 99%